Numerical Analysis of Diesel Engine Combustion and Performance with Single-Component Surrogate Fuel - Mehedi Hassan Pranta; Haeng Muk Cho (Energies)
Compression ignition engines are widely recognized for their reliability and efficiency, remaining essential for transportation and power generation despite the transition toward sustainable energy solutions. This study employs ANSYS Forte to analyze the combustion and performance characteristics of a direct-injection, single-cylinder, four-stroke engine fueled with an n-heptane-based diesel surrogate. The investigation considers varying SOI timings (−32.5°, −27.5°, −22.5°, and −17.5° BTDC) and EGR rates (0%, 15%, 30%, 45%, and 60%). The simulation incorporates the RNG k-ε turbulence model, the power-law combustion model, and the KH-RT spray breakup model. The results indicate that the optimal peak pressure and temperature occur at an SOI of −22.5° BTDC with 0% EGR. Advancing SOI enhances oxidation, reducing NOx and CO emissions but increasing UHC due to delayed fuel–air mixing. Higher EGR rates lower in-cylinder pressure, temperature, HRR, and NOx emissions while elevating CO and UHC levels due to oxygen depletion and incomplete combustion. These findings highlight the trade-offs between combustion efficiency and emissions, emphasizing the need for optimized SOI and EGR strategies to achieve balanced engine performance.